Searching Towards Creating a Sustainable Integrated Mesonet for the Canadian Prairie Provinces. Issue 5 (20th October 2019) - St-Jacques, Jeannine-Marie; Chipanshi, Aston; Hadwen, Trevor; Friesen, Allan; Sauchyn, David
ABSTRACT: We assess how weather events on the Canadian Prairies during the 2012 growing season were temporally and spatially represented by a high-resolution, non-World Meteorological Organization (WMO) standard private provider network, Earth Networks (EN), relative to the WMO standard climate stations operated by federal and provincial governments. We found that there was a large amount of missing station data in the EN network. We noticed the appearance of two significant patterns. The EN stations had higher hourly temperature values later in the day and higher daily T min than their nearest neighbouring governmental stations. The EN stations also recorded less 24-hour and 1-hour precipitation than their nearest neighbouring governmental stations. However, overall, the EN stations and the various governmental stations were complementary, often with one network being dense where the other one was sparse and vice versa, thereby giving a more spatially explicit picture of five storms during the 2012 growing season. Our ultimate objective is to show the benefits of including the high-resolution EN weather data, together with government station data, in a permanent, formally established, integrated mesonet for the Canadian Prairies, with the benefits of both the governmental station data and the private station data.